Diabetes and Stroke Prevention: A Review. (27th December 2012) - Hewitt, Jonathan; Castilla Guerra, Luis; Fernández-Moreno, María del Carmen; Sierra, Cristina
Abstract : Stroke and diabetes mellitus are two separate conditions which share multiple common threads. Both are increasing in prevalence, both are diseases which affect blood vessels, and both are associated with other vascular risk factors, such as hypertension and dyslipidemia. Abnormal glucose regulation, of which diabetes is one manifestation, is seen in up to two-thirds of people suffering from an acute stroke. Surprisingly, aggressive management of glucose after an acute stroke has not been shown to improve outcome or reduce the incidence of further strokes. More encouragingly, active management of other cardiovascular risk factors has been demonstrated to prevent stroke disease and improve outcome following a stroke in the diabetic person. Hypertension should be treated with a target of 140/80 mmHg, as a maximum. The drug of choice would be an ACE inhibitor, although the priority is blood pressure reduction regardless of the medication chosen. Lipids should be treated with a statin whatever the starting cholesterol. Antiplatelet treatment is also essential but there are no specific recommendations for the diabetic person. As these conditions become more prevalent it is imperative that the right treatment is offered for both primary and secondary prevention in diabetic people, in order to prevent disease and minimize disability.